(untitled) (Jalalabad Medical Journal, 2025)
Apert syndrome (Acrocephalosyndactyly) is a rare congenital disorder characterised by craniosynostosis, midfacial malformation, and symmetric syndactyly of the hands and feet. The prodromal characteristics for the typical cranio-facial appearance are early craniosynostosis of the coronal suture, cranial base, and agenesis of the sagittal suture. The reporting case presented with several cranio-facial deformities, including brachycephaly, midface hypoplasia, flat face, hypertelorism, ocular proptosis, down-slanting palpebral fissures, and syndactyly with osseous fusion of the hands and feet. Intraoral findings included a high arched palate with pseudocleft in the posterior one-third. Jalalabad Med J 2023; 20 (2): 72-75